Transgenic foods: Labelling and its lack of regulation in Peru - Vilchez Carrera, Lucero (2018)
The so-called Genetically Modified Organisms (GMOs) constitute a true revolution of biotechnology. The nutritional improvements at the genetic level represent the main objective for the production of “transgenic foods”. However, despite the benefits of using these techniques derived from research in cellular and molecular biology, this has not prevented taking into account safety issues related, mainly, to the packaging. Therefore, the present work raises some reflections on the new challenges facing the law before these new foods, specifically, in terms of labeling, based on what is established by international instruments and the experience given in developed countries, to finally provide a legislative initiative able to safeguard the fundamental rights of consumers.